2021
DOI: 10.3390/ijms22136838
|View full text |Cite
|
Sign up to set email alerts
|

5-HT3 Signaling Alters Development of Sacral Neural Crest Derivatives That Innervate the Lower Urinary Tract

Abstract: The autonomic nervous system derives from the neural crest (NC) and supplies motor innervation to the smooth muscle of visceral organs, including the lower urinary tract (LUT). During fetal development, sacral NC cells colonize the urogenital sinus to form pelvic ganglia (PG) flanking the bladder neck. The coordinated activity of PG neurons is required for normal urination; however, little is known about the development of PG neuronal diversity. To discover candidate genes involved in PG neurogenesis, the tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…For example, we find TNC expression to be specific to the vagal neural crest ( Figure 1C and D ), consistent with its requirement for migration into the hindgut by changing the extracellular microenvironment ( Akbareian et al, 2013 ). In addition, the sacral neural crest expresses high levels of SOX10-mediated Cdh19 ( Huang et al, 2022 ), as well as Pax3 and 5-HT3 for innervation and neuronal maturation in the pelvic ganglion ( Deal et al, 2021 ; Ritter et al, 2021 ). Ret is also known to be upregulated in vagal neural crest cells to mediate more invasive behavior than in sacral neural crest ( Delalande et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, we find TNC expression to be specific to the vagal neural crest ( Figure 1C and D ), consistent with its requirement for migration into the hindgut by changing the extracellular microenvironment ( Akbareian et al, 2013 ). In addition, the sacral neural crest expresses high levels of SOX10-mediated Cdh19 ( Huang et al, 2022 ), as well as Pax3 and 5-HT3 for innervation and neuronal maturation in the pelvic ganglion ( Deal et al, 2021 ; Ritter et al, 2021 ). Ret is also known to be upregulated in vagal neural crest cells to mediate more invasive behavior than in sacral neural crest ( Delalande et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…The localization of the 5-HT 3 receptor at different organs has implications for signal pathways. For example, 5-HT 3 receptors in the colon induced colonic inflammation through substance P (SP) and the neurokinin-1 (NK1) receptor, and 5-HT 3 receptors signaling the neural crest (NC) alter the development of the visceral organs, including the lower urinary tract (LUT) [70,71]. At the cellular level, most studies show functional receptors at the plasma membrane, although one study indicated the presence of a functional 5-HT 3 receptor on mitochondria; however, the exact location was not pinpointed [36].…”
Section: Discussionmentioning
confidence: 99%
“…For example, we find Tnc expression to be specific to the vagal neural crest (Fig 1C, D), consistent with its requirement for migration into the hindgut by changing the extracellular microenvironment 22 . In addition, the sacral neural crest expresses high levels of Sox10 -mediated Cdh19 23 , and well as Pax3 and 5-HT3 for innervation and neuronal maturation in the pelvic ganglion 24, 25 . Ret is also known to be upregulated in vagal neural crest cells to mediate more invasive behavior than in sacral neural crest 26 .…”
Section: Discussionmentioning
confidence: 99%